Age, body composition parameters and glycaemic control contribute to trabecular bone score deterioration in acromegaly more than disease activity - Ságová, Ivana; Mokáň, Marián; Tonhajzerová, Ingrid; Rončáková, Marianna; Vaňuga, Peter (Frontiers in Endocrinology, 2023)
Introduction: Impairment of bone structure in patients with acromegaly (AP) varies independently of bone mineral density (BMD). Body composition parameters, which are altered in patients with acromegaly, are important determinants of bone strength.The aim of this study was to examine BMD and lumbar trabecular bone score (TBS) by dual-energy X-ray absorptiometry (DXA) and to assess its relationship with disease activity, age, glucose metabolism, and body composition parameters.This cross-sectional prospective study involved 115 patients with acromegaly (70 F, 45 M) and 78 healthy controls (CON) (53 F, 25 M) matched for age, gender, and BMI. Bone mineral density, TBS and body composition parameters were measured using DXA.Results: AP presented with lower TBS compared to CON (1.2 ± 0.1 v 1.31 ± 0.1, P< 0.001).No significant correlation was observed between IGF-1/GH levels and TBS. Age, glycated haemoglobin, BMI, waist circumference, fat mass, and lean mass negatively correlated with TBS in both sexes. Multiple linear regression analysis of all these parameters revealed age and waist circumference as independent significant predictors of TBS in AP. We did not find difference in BMD (lumbar and femoral sites) between AP and CON nor between active and controlled AP. We observed negative correlation between age and BMD of the femoral neck and total hip (P < 0.001). Testosterone levels in males, BMI, waist circumference, fat mass, and lean mass positively correlated with BMD in AP, with stronger correlation between lean mass and BMD compared to fat mass.Patients with acromegaly have lower TBS than controls, confirming impaired bone microarchitecture in acromegaly regardless of BMD. Age, body composition parameters and glucose metabolism contribute to TBS deterioration in AP more than disease activity itself.